Continuum of neurobehaviour and its associations with brain MRI in infants born preterm. Issue 1 (5th October 2017) - Eeles, Abbey L; Walsh, Jennifer M; Olsen, Joy E; Cuzzilla, Rocco; Thompson, Deanne K; Anderson, Peter J; Doyle, Lex W; Cheong, Jeanie L Y; Spittle, Alicia J
Abstract : Background: Infants born very preterm (VPT) and moderate-to-late preterm (MLPT) are at increased risk of long-term neurodevelopmental deficits, but how these deficits relate to early neurobehaviour in MLPT children is unclear. The aims of this study were to compare the neurobehavioural performance of infants born across three different gestational age groups: preterm <30 weeks' gestational age (PT<30); MLPT (32–36 weeks' gestational age) and term age (≥37 weeks' gestational age), and explore the relationships between MRI brain abnormalities and neurobehaviour at term-equivalent age. Methods: Neurobehaviour was assessed at term-equivalent age in 149 PT<30, 200 MLPT and 200 term-born infants using the Neonatal Intensive Care UnitNetwork Neurobehavioral Scale (NNNS), the Hammersmith Neonatal Neurological Examination (HNNE) and Prechtl's Qualitative Assessment of General Movements (GMA). A subset of 110 PT<30 and 198 MLPT infants had concurrent brain MRI. Results: Proportions with abnormal neurobehaviour on the NNNS and the HNNE, and abnormal GMA all increased with decreasing gestational age. Higher brain MRI abnormality scores in some regions were associated with suboptimal neurobehaviour on the NNNS and HNNE. The relationships between brain MRI abnormality scores and suboptimal neurobehaviour were similar in both PT<30 and MLPT infants. The relationship between brain MRI abnormality scores and abnormal GMA was stronger in PT<30 infants. Conclusions: There was a continuum of neurobehaviour across gestational ages. The relationships between brain abnormality scores and suboptimal neurobehaviour provide evidence that neurobehavioural assessments offer insight into the integrity of the developing brain, and may be useful in earlier identification of the highest-risk infants.